Length – Weight Relationships, Meat Yield and Morphometric Indices of Five Commercial Bivalve Species Collected from the Çanakkale Strait (Türkiye) - İbrahim Ender Künili; Fatma Çolakoğlu; Serhat Çolakoğlu (Aquatic Sciences and Engineering)
This study was conducted to determine the meat yield, morphometric characteristics, length– weight relationships (LWRs) and their correlations with environmental variables of five commercial bivalve species collected monthly between 2014 and 2015 from the coastal waters of the Çanakkale Strait. A total of 8588 individuals were examined, and different ranges for both shell length (9.00- 108.50 mm) and total weight (0.30-234.20 g) were determined according to species. The highest meat yields from Donax trunculus (16.40-23.34%), Mytilus galloprovincialis (14.89-34.35%) and Ostrea edulis (5.91-26.24%) were determined in spring, while Ruditapes philippinarum (10.80- 29.53%) and Chamelea gallina (12.26-18.92%) had maximum yield in late summer and early autumn (p<0.05). Elongation index (SH/SL), compactness index (SW/SL), convexity index (SW/SH), and density indexes (TW/SL) were significant (p<0.05) and had high correlation coefficients (r=0.806- 0.975). The mean value of the allometry coefficient (b) was 3.257±0.168, ranging from 2.291 to 4.058. Four species had negative allometries, namely D. trunculus (2.738), C. gallina (2.889), M. galloprovincialis (2.597) and O. edulis (2.728), while R. philippinarum (3.137) displayed positive allometry. The morphometric indices show high morphological resemblances. As a result, it is thought that the data obtained in this study can both provide data in the fields of biology and ecology for current scientific studies on these species, and can be used as a resource for the sustainable production of these commercial species.